The Development of the Human Mindset Towards the Advancement of Science, Technology And Science - Mahardika, I Ketut; Mahmudi, Kendid; Sholihah, Faiqotus; Kusumawati, Ika Nur; Kinantaka, Arjunanda Tri Bagus; Yasinta, Rensi Rima (International Journal of Education, Information Technology, and Others, 2024)
This article explains how the development of mindset in humans can have an impact on the progress of science and technology. This article's research is to provide an understanding of what factors influence the development of mindset in humans to what impact on the progress of science and technology. This type of research is a literature review that comes from various kinds of literature that have a relationship with the development of mindset on the development and progress of science and technology.